Identification of the Carbohydrate and Organic Acid Metabolism Genes Responsible for Brix in Tomato Fruit by Transcriptome and Metabolome Analysis - Li, Ning; Wang, Juan; Wang, Baike; Huang, Shaoyong; Hu, Jiahui; Yang, Tao; Asmutola, Patiguli; Lan, Haiyan; Qinghui, Yu (Frontiers in Genetics, 2021)
Background Sugar and organic acids not only contribute to the formation of soluble solids (Brix) but also are an essential factor affecting the overall flavor intensity. However, the possible metabolic targets and molecular synthesis mechanisms remain to be further clarified. Methods UHPLC-HRMS (ultrahigh-performance liquid chromatography and high-resolution mass spectrometry) combined with comparative transcriptome analysis were performed in fruits at green ripe (S1), turning-color (S2), and red ripe (S3) stages of two tomato genotypes TM-1 (Solanum galapagense L., LA0436) and TM-38 (S. lycopersicum L. cultivar M82, LA3475) that vary in fruit Brix. Results The fruit Brix of TM-1 was nearly twice that of TM-38 at S3. Nevertheless, TM-1 accumulated 1.84- and 2.77-fold the L-malic acid and citric acid in red ripe fruit (S3) compared with TM-38, respectively. D-glucose and D-fructose in TM-1 and TM-38 fruits tended to be similar at S3. Concomitantly, the sugar/organic acid ratio of TM-38 fruits were 23. 08-, 4. 38-, and 2.59-fold higher than that of TM-1 fruits at S1, S2, and S3, respectively. Among starch and sucrose (carbohydrate, CHO) metabolism (ko00500) genes, SUS (Solyc07g042550.3) and BAM (Solyc08g077530.3) were positively (r = 0.885–0.931) correlated with the sugar/organic acid ratio. Besides, INV (Solyc09g010080.3 and Solyc09g010090.5.1), AAM (Solyc04g082090.3), 4-α-GTase (Solyc02g020980.2.1), BGL2 (Solyc06g073750.4, Solyc06g073760.3, and Solyc01g081170.3), TPS (Solyc01g005210.2 and Solyc07g006500.3), and TPP (Solyc08g079060.4) were negatively (r = −0.823 to −0.918) correlated with the sugar/organic acid ratio. The organic acid (TCA cycle) metabolism (ko00020) gene ALMT (Solyc01g096140.3) was also negatively (r = −0.905) correlated with the sugar/organic acid ratio. Conclusion Citric acid may play a more dominant role in the sugar/organic acid ratio of the tomato fruit, and the contribution of both L-malic acid and citric acid to the fruit Brix was much greater than that of D-glucose and D-fructose. Genes involved in CHO and TCA metabolism, which have a significant correlation with the sugar/organic acid ratio were considered to be the contributing factors of fruit Brix.